2018
DOI: 10.1002/jemt.23032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia inducible factors on pluripotency in human iPS cells

Abstract: A hypoxic condition is known to contribute to pluripotency. In the present article, the effects of transcription factors were first assessed regarding the proliferation and differentiation of human induced pluripotent stem (iPS) cells under hypoxic conditions using cell morphology and real-time polymerase chain reaction (RT-PCR). Morphology evaluations and RT-PCR revealed that the colony formation was promoted and the expression of pluripotent markers was increased under hypoxic conditions. In addition, the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…However, the effect of low oxygen tension on such parameters as cell growth and the expression of pluripotency markers differs among various studies, as summarized in Table 1. Most of the available data show accelerated cell growth under hypoxic conditions [19,20,37,40] and enhanced expression of pluripotency markers, OCT4, SOX2, NANOG [20,40,48]. Our own results stayed in line with these observations, supporting the beneficial role of a low oxygen condition in the maintenance of pluripotency in hiPSCs (Figure 2).…”
Section: Hypoxia Affects Hpscs Culture In Vitrosupporting
confidence: 83%
See 3 more Smart Citations
“…However, the effect of low oxygen tension on such parameters as cell growth and the expression of pluripotency markers differs among various studies, as summarized in Table 1. Most of the available data show accelerated cell growth under hypoxic conditions [19,20,37,40] and enhanced expression of pluripotency markers, OCT4, SOX2, NANOG [20,40,48]. Our own results stayed in line with these observations, supporting the beneficial role of a low oxygen condition in the maintenance of pluripotency in hiPSCs (Figure 2).…”
Section: Hypoxia Affects Hpscs Culture In Vitrosupporting
confidence: 83%
“…It has been demonstrated that physiological hypoxia (3-5% O 2 ) supports an undifferentiated state of hPSCs, and decreases the rate of spontaneous differentiation, which can be observed as areas of flattened and enlarged cells with translucent cytoplasm localized at the periphery of the colonies. Such areas are smaller or absent under hypoxic conditions, compared to normoxia (21% O 2 ) [19,20,36,40,46]. Importantly, hypoxia was crucial to the maintenance of inactivated X chromosomes in hESCs, which is an indicator of naïve pluripotency [47].…”
Section: Hypoxia Affects Hpscs Culture In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been demonstrated that the high degree of cross-linking inside a polymer network decreases diffusion of water, ions, and small molecules which might interfere with cell growth 59 . Furthermore, oxygen pressure has been shown to be an influencing factor in the differentiation process of stem cells 60,61 . However, as the fibrin gels that we generated were very thin (1–2 mm in depth), it is unlikely that the cells inside fibrin gel experienced severe hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%